Differences in Tetracycline Antibiotic Resistance Genes and Microbial Community Structure During Aerobic Composting and Anaerobic Digestion - Luo, Luyun; Zhang, Chengjia; Zhang, Zhuo; Peng, Jing; Han, Yongqin; Wang, Pei; Kong, Xiaoting; Rizwan, Hamid Muhammad; Zhang, Deyong; Su, Pin; Liu, Yong (Frontiers in Microbiology, 2020)
Antibiotics are widely added to swine forage and are the main reason for the environmental accumulation of antibiotic resistance genes (ARGs) in swine manure-dwelling microorganisms. Aerobic composting (AC) and anaerobic digestion (AD) are efficient methods for converting swine manure to bio-fertilizer while degrading residual antibiotics. However, the influence of these methods on ARG accumulation and the difference in their efficiency have rarely been investigated. In this study, we explored the variations in four tetracycline antibiotics (TCs) and their associated ARGs and in microbial communities after AC and AD treatment. After full-scale manure AC and AD, the four TCs were removed effectively. AD had a higher TC removal efficiency than AC and a slower rate of TC-associated ARG accumulation. In addition, the community structure was more stable in the AC and AD manures than in untreated manure, and the relationship among microbial species also evolved into competition from mutualism after both AC and AD treatment. It was also speculated that the genera Acholeplasma and Arthrobacter were the possible hosts of tetO, tetW, and tetQ; the shift in the prokaryotic community composition and the alleviation of selective pressure by TC degradation led to decreased relative abundance of ARGs in AD- and AC-treated manure.